Utilizing Artificial Intelligence to Support Teacher Administration and Improve Education Quality - Nelly Rahmawati Ningsih; Diana Sarah; Eny Tantia Finorita; Muhtadin Muhtadin; Dessy Ari Lestari; Maman Suryaman (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the role of artificial intelligence (AI) in supporting teachers’ learning administration and its implications for work efficiency and educational service quality in Karawang Regency. The research employs a qualitative literature review design, drawing data from national and international journals, academic books, conference proceedings, and relevant educational policy documents published over the last decade. Data analysis was conducted using thematic analysis, involving systematic literature selection, coding, categorisation, and theme development related to AI implementation, its impacts, and challenges in educational administration. The findings reveal that AI is utilised in various administrative activities, including grade processing, attendance management, electronic report card generation, academic documentation management, and real-time monitoring of student learning progress. The use of AI significantly improves teachers’ work efficiency by reducing administrative workloads, minimising data entry errors, and enhancing the accuracy and transparency of academic information. Consequently, teachers are able to allocate more time and attention to instructional planning and classroom learning activities. Despite these benefits, several challenges persist, such as inadequate digital infrastructure, disparities in teachers’ digital literacy, and concerns regarding student data security and privacy. Overall, the study concludes that AI integration in educational administration holds strong potential to improve educational service quality when supported.